Economics of the public sector - Stiglitz, Joseph E (W. W. Norton, 2000)
The book is organized into six parts. First, part one introduces fundamental questions, institutional details, and a review of the microeconomic theory underlying the role of the public sector. Prat two develops the theory of public expenditures, including public goods, public choice, and bureaucracy, while part three applies the theory to the five largest areas of public expenditure in United Staes: health, defense, education, social security, and wafare programs. Parts four and five repeat this pattern, presenting the theory of taxation and its analysis, respectively. Part six takes up two further topicas: issues concerning state and local taxation and expenditure and fiscal federalism; and issues concerning stabilization and growth, with particular emphasis on the relation between microeconomic analysis and macroeconomic performance